How ASEAN4 Conventional, Islamic, and ESG Indices React to Twitter Market Uncertainty? - Zaheer Anwer (Bank Indonesia, 2025)
We investigate the time varying return spillover of ASEAN4 asset classes from four countries including Thailand, Philippines, Malaysia and Indonesia, and Twitter based market uncertainty measure, using daily data from 01-Sep-2014 to 21-Apr-2023. The estimations are performed using TVP-VAR approach. The results reveal that the dynamic connectedness of ASEAN4 markets fluctuates significantly. It peaked during bearish periods (2015-2016 and 2020) and remained low during market booms (2017-2018 and 2022). Islamic and ESG indices exhibit patterns similar to conventional indices. Indonesia and Malaysia emerge as net shock transmitters until the pandemic, with Thailand becoming a net transmitter post-COVID. Thailand’s role shifts between receiver and transmitter based on economic conditions relative to other ASEAN countries. Twitter Market Uncertainty Index (TMUENG) primarily remains a receiver, with limited impact on ASEAN4 Conventional, Islamic, and ESG indices. The findings are robust to a battery of robustness tests and carry important policy implications for investors and policymakers.